The ethical and legal implications of deactivating an implantable cardioverter-defibrillator in a patient with terminal cancer. Issue 9 (30th August 2007) - England, Ruth; England, Tim; Coggon, John
Abstract : In this paper, the ethical and legal issues raised by the deactivation of implantable cardioverter-defibrillators (ICDs) in patients with terminal cancer is considered. It is argued that the ICD cannot be well described either as a treatment or as a non-treatment option, and thus raises complex questions regarding how rules governing deactivation should be framed. A new category called "integral devices" is proposed. Integral devices require their own special rules, reflecting their position as a "halfway house" between a form of treatment and a part of the body. The practical problems faced by doctors working in palliative medicine with regard to the deactivation of ICDs are also considered.